A new DC-AC Interconnected Cascaded converter (ICC) with sinusoidal output voltage over a wide frequency range - Ahmed Allehyani; Ahmed Morsy; Prasad Enjeti (Alexandria Engineering Journal, 2023)
In this paper a new dc to ac Interconnected Cascaded Converter (ICC) is presented. The proposed ICC consists of several modular submodules of two switches and an inductor interconnecting two capacitors. Each submodule is controlled to keep the voltage on each capacitor as a slice of a sinewave. The output voltage of the converter, according to KVL, includes the sum of the voltages on the capacitor that represents a full pure sinewave. The sinusoidal output of the converter can be varied over a wider range. The proposed converter has the following advantages: sinusoidal output voltage with v/f control; absence of dv/dt related issues; compact size/weight/volume due to the use of wide band gap switching devices. The converter is modular in construction, employs high frequency L-C components and semiconductor switches can be stacked for voltage sharing. The proposed converter is a promising candidate for multiple applications such as high performance ac motor drives, microinverters and uninterruptible power supplies, carbon neutral logistics and electric vehicles. The paper details the operating modes, control aspects along with an illustrative design example for a three and eleven module converter. Experimental results on a laboratory prototype converter employing 600 V GaN devices are discussed.